Efficiency Issue and Its Relation to Labour/Worker - Ibrahim, Muhamad Fithri; Kee, Daisy Mui Hung; Bin Shamsul Hisham, Danish Ikhwan; Bin Azahar, Muhd Amir Firdaus; Bin Wan Abdullah, Wan Muhammad Arif; Alfares, Omar A (AIBPM Publisher, 2019)
The purpose of the research to illustrate the relationship between efficiency issues and labour/worker in McDonalds. This research would be using quantitative and qualitative research method together. For the qualitative method is interview. The interview would be collected via email that been using to communicate with the company and individual interviews with a small number of respondents such as McDonalds manager to explore their perspectives on labour/worker efficiency. Second, quantitative method is questionnaires would distribute to targeted segment about their view on productivity. The collected data would be analysing and finalize the result of the research. Labour is part of main factor that might influence the movement of productivity in the company and it is also depends on labour efficiency. Poor productivity happened in McDonald is because of poor labour management. In this research, we will also debunk the factor that leads problems of labour productivity. Listed below are some factor might affect labour productivity or efficiency on their works. The factors are such as Overtime, Morale and attitude, Absenteeism and Turnover, Errors and Omission and Reassignment of Manpower. The factor that have been listed are not finalised yet and would be review and analyse whether it is some others factor that happen at McDonald’s labour. The data that we will collect will be present by graph. From the graph the data can be interpret and present easier. In conclusion, company must gather the factor that affecting labour productivity, so they can immerse their employee in efficient working environment and contribute in economic growth of the company